A comparative analysis of the rehabilitation course of two patients after the implantation of an artificial hip joint - Handkiewicz, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Endoprosthetics is the most effective method of returning to a normal way of life without pain. The key element is the post-operative rehabilitation program where a patient has to comply with certain rules and principles. The rehabilitation also includes the family of the patient. Each person, after any surgery requires an individual approach, and no patient can be commonly treated. Aim. The aim of the article is to compare the effects of an early rehabilitation after the implantation of an artificial hip joint in two patient cases. Description of the cases. This research was conducted at Bodden-Klinken GmbH. An individual case study was used, based on an example of two patients at the age of 59 who had implantation of an artificial hip joint. The carried out rehabilitation of the patients was conducted without any disruptions. Patients were able to freely walk on crutches nine days after the procedure. Conclusions. In the cases analyzed, the rehabilitation course was described until the ninth day after implantation of an artificial hip joint. High results in terms of patient rehabilitation were achieved. Furthermore, in order to continue their therapy, they were referred to the sanatorium.
Keywords: artificial hip joint; rehabilitation; post-surgical rehabilitation